Presentation Performance: Transforming Anxiety to Confidence of EFL Students in Classroom Seminar at Higher Education Context - Nurdevi Bte `Abdul; Andi Mukarramah Nagauleng; Herlina Daddi (Newinera Publisher, 2026)
Anxiety in the classroom, especially in presentation has a debilitating effect on students’ performance, academic development, success in learning a foreign language. Some of the students could deliver their speaking fluently and influentially. This study is limited to the aim at exploring cause of anxiety in seminar presentation, and explore the ways to be confident in presentation. The participants consisted of 3 non-native English lecturers who teach Seminar in ELT course and ten students involved in this study; five students who have anxiety problems, and five students who have good confident in classroom presentation. They were advanced students in seventh semester. Observation and interview were used to collect the data. The data were analysed in a linear hierarchical approach building from the bottom to the top. The raw data were organized and prepared for analysis. This involves transcribing interviews typing up field notes, sorting and arranging the data into different types depending on the sources of information. Dealing with the aims of the study, results revealed presentation anxiety is caused by lack of preparation, fear of audience’s judgment, personality problems, language mastery, and academic demands; the suggested ways in mitigating anxiety to be confident in classroom presentation are drilling practice, doing preparation, getting feedback, strengthening concept, and expressing nonverbal communication. Thus, the transformation of presentation anxiety to confidence occurs through interrelated process of cognitive, affective, and psychometric practices.